Molecular Docking of Active Compounds from The Ethanol Extract of Phaleria macrocarpa Fruit with Iron Transporters DMT1 and ZIP14 - Rahma, Rahma; Estuningtyas, Ari (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2024)
Iron-overload can lead to organ damage by promoting free radical production.This study explores the potential inhibitory effects of compounds found in Phaleria macrocarpa fruit on non-transferrin-bound iron uptake by targeting DMT1 and ZIP14 iron transporters through in-silico methods.The study utilized homology modeling to construct 3D structures of DMT1 and ZIP14. Validation of these models was carried out by assessing their sequence identity and analyzing their stereochemical quality using Ramachandran plots. Molecular docking was conducted using AutoDockTools. The coordinates for molecular docking were carefully chosen based on the iron binding-site locations as reported in previous literature. Interaction visualization was done using LigPlot+. Our findings indicate strong binding affinities of several compounds from Phaleria macrocarpa fruit with both DMT1 and ZIP14. Specifically, patuletin-7-O-[6